2010
DOI: 10.1111/j.1751-553x.2010.01223.x
|View full text |Cite
|
Sign up to set email alerts
|

Race‐specific WBC and neutrophil count reference intervals

Abstract: Healthy African Americans are known to have reduced white blood cell counts (WBC) and absolute neutrophil counts (ANC) compared with European Americans, with little agreement about the levels in reference intervals. The objective is to establish race-specific reference intervals for WBC and ANC using US National Health and Nutrition Examination Survey (NHANES) of 2000-2003. A total of 14,184 civilian noninstitutionalized US citizens participated in NHANES 2000-2003 had complete blood count, red cell distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
55
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(67 citation statements)
references
References 15 publications
10
55
1
1
Order By: Relevance
“…To explain initial longer telomere length observed in Blacks, several researchers have noted that white blood cell admixture differs by race (Lim, Cembrowski, Cembrowski, & Clarke, 2010),. Zhu and colleagues found that Black individuals have longer LTL in adolescence, and Hunt and colleagues present cross-sectional data that suggested LTL was longer in Blacks vs.…”
Section: Discussionmentioning
confidence: 99%
“…To explain initial longer telomere length observed in Blacks, several researchers have noted that white blood cell admixture differs by race (Lim, Cembrowski, Cembrowski, & Clarke, 2010),. Zhu and colleagues found that Black individuals have longer LTL in adolescence, and Hunt and colleagues present cross-sectional data that suggested LTL was longer in Blacks vs.…”
Section: Discussionmentioning
confidence: 99%
“…One potential mechanism might be related to the low WBC count seen in blacks. 20 While low WBC counts have not conferred an increased nosocomial infection risk amongst blacks generally, it may potentially influence the susceptibility to post-stroke immunodepression. Infections were also more common in deep hemorrhages, which were more common in blacks, than in lobar hemorrhages.…”
Section: Discussionmentioning
confidence: 99%
“…Endemic goiters are seen in both mountainous (New Guinea) and non-mountainous regions of Africa (Cameroun, Northern Zaire, Central Africa Republic, Uganda, and Rwanda). The prevalence rates of endemic goiters in Africa range from 1% to 90% [19]. None of these common textbooks made reference to any of the above facts.…”
Section: Areas Of Lapses In Physiology Textbook For Africamentioning
confidence: 99%